Individual Variation in Pragmatic Comprehension of Finnish Learners of English: A Three-Week Language Course Abroad as a Learning Context - Jompero, Meri (My University, 2017)
This MA thesis studied seven Finnish learners of English participating in a three-week language course abroad. The purpose of the study was to examine how a three-week language course abroad affected the Finnish learners’ pragmatic comprehension. The objective was to understand the relationship between the learners’ backgrounds, their language learning, their experiences in the study abroad environment and their outcomes of pragmatic comprehension during a three-week language course in the United States. This study was a mixed method study combining both quantitative and qualitative methods. The data were collected by using a test of pragmatic comprehension before and after the course. The test was a multiple-choice questionnaire measuring the knowledge of routines, implicatures, and speech acts (refusals, requests and apologies). In addition to the tests, the participants were asked to keep a journal twice during the course. They were also interviewed after the course. The study did not test a certain hypothesis or a theory because the learners’ own experiences and perspectives were thought to provide a more in-depth understanding of the phenomenon. The methods of content analysis were used to analyze the data and find patterns in the participants’ perspectives. When the test results were treated as a group, it seemed that pragmatic comprehension improved during the language course in the U.S. However, when taking a closer look at the results, there were variations between the learners as three learners scored higher results, three scored lower, and one’s results remained the same. Based on the analysis, various factors seemed to be effective in terms of either noticing or learning of pragmatic features in the target language country. The external factors were related to opportunities to interact in English in a study abroad context, learning in foreign language classrooms and in informal learning situations outside classrooms. Internal factors were related to motivation, positive attitudes towards the L2 culture and language, language anxiety, and L2 proficiency.